Monitoring of the oral cavity after fixing the veneers (LLC "Endo Press", 2020)
The hygienic state of the oral cavity and the degree of bleeding of the gums after fixing the veneers were estimated. Veneers were installed in 93 patients, the average age was 30.2 ± 5.12 years. In 59.1% of cases, ceramic (group 1) was established, in 40.9% cases - composite veneers (group 2). Indices of OHI-S, GI and SBI were determined in the oral fluid. The state of oral hygiene in both groups improved by an average of 23.7% and 19.0%, respectively, in groups 1 and 2, 10-14 days later, compared with baseline. A month later the difference was 90.0% (p